1994
DOI: 10.1172/jci117046
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of postischemic acute renal failure with a selective endothelinA receptor antagonist in the rat.

Abstract: Studies were designed to examine the effect of a selective endothelinA (ETA) receptor antagonist, BQ123, on severe postischemic acute renal failure (ARF) in Sprague-Dawley rats. Severe ARF was induced in uninephectomized, chronically instrumented rats by 45-min renal artery occlusion. BQ123 (0.1 mg/kg. min) or vehicle was infused intravenously for 3 h on the day after ischemia. Measurements before infusion (24 h control) showed a 98% decrease in glomerular filtration rate (GFR), increase in fractional excretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
90
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(97 citation statements)
references
References 26 publications
4
90
0
3
Order By: Relevance
“…Recent studies indicated that the ET-1/ET A receptor system may be an important mediator in the pathogenesis of postischemic acute renal failure, based on findings that ET-1 mRNA expression is markedly enhanced in the postischemic kidney 32 and that a selective ET A receptor antagonist prevents postischemic renal damage, such as decreases in renal blood flow and glomerular filtration rate, and tubular dysfunction. 11,12 Further investigations are required to clarify whether the ABT-627-induced improvement in vascular hypertrophy and renal damage in DOCA-salt hypertension is independent of its antihypertensive activity.…”
Section: Matsumura Et Al February 1999 763mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated that the ET-1/ET A receptor system may be an important mediator in the pathogenesis of postischemic acute renal failure, based on findings that ET-1 mRNA expression is markedly enhanced in the postischemic kidney 32 and that a selective ET A receptor antagonist prevents postischemic renal damage, such as decreases in renal blood flow and glomerular filtration rate, and tubular dysfunction. 11,12 Further investigations are required to clarify whether the ABT-627-induced improvement in vascular hypertrophy and renal damage in DOCA-salt hypertension is independent of its antihypertensive activity.…”
Section: Matsumura Et Al February 1999 763mentioning
confidence: 99%
“…8,9 We noted the ameliorating effect of FR 139317, an ET A -selective receptor antagonist, on decreased renal function of DOCAsalt hypertensive rats. 10 On the other hand, both ET A -selective and nonselective ET A /ET B receptor antagonists have been reported to prevent various cardiovascular diseases, such as acute ischemic renal failure [11][12][13] and chronic heart failure, 14,15 in animal models. Thus, it remains obscure as to whether blockade of the ET B receptor is beneficial for the treatment of subjects with cardiovascular diseases.…”
mentioning
confidence: 99%
“…To date, the results indicate that ischemia-induced ARF is attenuated by the infusion of anti-endothelin antibody or a receptor antagonist during ischemia or the early phase of reperfusion. In a recent study, however, BQ-123 infused 24 hr after the onset of ischemia was shown to effectively reverse renal damage in rats with ARF, clearly indicating that an ETA antagonist is efficacious even in the treatment of established ARF (182). Furthermore, since the negative actions of endothelin-1 on renal function in ARF are more marked during the maintenance phase than the initial phase after ischemia, endothelin receptor antagonists appear to be more effective in reversing than in preventing renal impairment (183,184).…”
Section: V-3 Acute Renal Failurementioning
confidence: 96%
“…At least five studies have shown that ET-1 receptor blockade either conferred no functional protection, or worsened post-ischemic AKI [36][37][38][39][40]. In a more recent ischemia-reperfusion model in mice undergoing unilateral ischemia without contralateral nephrectomy, an increase in intrarenal ET-1 production was observed, along with increased expression of the ET A receptor and evidence of ET-1 gene activation alongside progressive histological changes and a 40% loss of renal mass [41].…”
Section: Endothelin-1mentioning
confidence: 99%